THE EFFECT OF REGIONAL TAXES, REGIONAL RETRIBUTIONS, BALANCED FUNDS AND REGIONAL EXPENDITURE ON REGIONAL FINANCIAL PERFORMANCE OF REGENCY/CITY GOVERNMENTS IN NORTH SUMATRA - Benny Rojeston Marnaek Nainggolan; Tesalora Veronika Sinaga; Ayu Natalia Siagian; Rika Dorlina Siahaan; Dokman Marulitua Situmorang (SEAN Institute, 2023)
This study aims to determine: (1) The effect of local taxes on regional financial performance, (2) The effect of regional levies on regional financial performance, (3) The effect of balancing funds on regional financial performance, (4) The effect of regional spending on regional financial performance, (5) The influence of local taxes, balancing funds, and regional spending on regional financial performance. The population in this study is annual data from 2016-2020 by taking the financial reports of the Regional Revenue and Expenditure Budget (APBD) in North Sumatra. The sample in this study amounted to 33 districts/cities with sampling using saturated sampling technique. The data collection method used is a documentation technique, namely collecting data through the official BPS website.